If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(3r + 6) = -90 Reorder the terms: -6(6 + 3r) = -90 (6 * -6 + 3r * -6) = -90 (-36 + -18r) = -90 Solving -36 + -18r = -90 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -18r = -90 + 36 Combine like terms: -36 + 36 = 0 0 + -18r = -90 + 36 -18r = -90 + 36 Combine like terms: -90 + 36 = -54 -18r = -54 Divide each side by '-18'. r = 3 Simplifying r = 3
| -8+8(a-5)= | | 4x+10yz-3=0 | | -5(3x+3)+4=-71 | | 4(1+4k)-3= | | 5((1/2)-3) | | (12x+66)+(2x+20)=9 | | 2(3f+1)= | | -6(1+6x)-1= | | 4n+3(6n-1)=-135 | | 5(1/2-3) | | 2x-17=7x+12 | | 10x+9=7x+8 | | 8p+4=7+7p | | cx+b=5(x-c) | | 4-(3n-3)= | | -14y+28+6x=-44 | | -5*a+(-5*b)=3 | | 32+0.25y=50 | | log(x)=-22.7 | | 1/2•32= | | -268=12(x)-4 | | 8b+8(1-8b)= | | -268=4-12(x) | | 5/9x3/15 | | F(3)=1/2•32 | | 2x+-9(2)=9 | | 4-12(x)=-268 | | 2x+-9(0)=9 | | 9(12/7)+7= | | .55=log(x) | | 3x-6x+6=x-5+11 | | -4m-7(6m-4)= |